Defining extreme hardship to determine eligibility to welfare aid: The shift from household income measurement to means testing - Zacharias, Rodrigo; Grano Haik, Cristiane Fátima; Bueno de Azevedo, Paulo (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2022)
This paper discusses extreme hardship as an economic eligibility requirement to the welfare aid set forth in Article 20, paragraph 3, of Law 8.742/1993. The analysis is based on criteria that go beyond the measurement of monthly per capita household income and adopts a deductive approach to scrutinize the literature, legislation, and case law on the subject. The paper maps out the development of the relevant cases and provides insight into the precedents laid down by the Federal Supreme Court. The problems posed by the subsidiary nature of the benefit are also considered. All in all, monthly per capita household income not being an accurate indicator of extreme hardship, the means test should be adopted.